Pengaruh Sistem Pembayaran Elektronik Terhadap Inflasi Di Indonesia - Rosanti, Octavia; Maulida, Sri (Forum Kerjasama Pendidikan Tinggi, 2022)
This research aims to determine the effect of Electronic Money, Credit Card and Debit Card variables on Inflation in Indonesia. The data used is secondary data accessed from the Bank Indonesia website. This research uses monthly time series data from January 2019 to December 2021. The research method used in this research is Multiple Linear Regression using the SPSS application. The results of the research show that the Electronic Money variable has no significant and negative effect on Inflation in Indonesia, the Credit Card variable has a significant and positive effect on Inflation in Indonesia and the Debit Card variable has a significant but negative effect on Inflation in Indonesia. Then the variables of Electronic Money, Credit Cards and Debit Cards have a significant influence on Inflation in Indonesia.